NF-κB-mediated anti-inflammatory effects of an organic light-emitting diode (OLED) device in lipopolysaccharide (LPS)-induced in vitro and in vivo inflammation models - Mo, SangJoon; Kim, Eun Young; Kwon, Yi-Suk; Lee, Min Young; Ahn, Jin Chul (Frontiers in Immunology, 2022)
Inflammation is the body’s physiological response to harmful agents. However, if not regulated properly, inflammation can become pathological. Macrophages are key players in the inflammatory process, and modulate the immune response. Due to the side effects of anti-inflammatory drugs, non-pharmaceutical therapies for inflammatory diseases must be developed. Photobiomodulation is a non-invasive therapeutic approach to treating certain pathological conditions using light energy. Light-emitting diodes (LEDs) are commonly used as light sources for photobiomodulation treatment, but their clinical applications are limited. Organic LEDs (OLEDs) are thin, lightweight and flexible, enabling consistent and even delivery of light energy to target areas; this makes OLED promising components for therapeutic devices. In the present study, we examined the effects of OLED treatment on inflammation in vitro using a lipopolysaccharide (LPS)-induced macrophage RAW264.7 cell model, and in vivo using a pinna skin mouse model. We found that LPS-induced morphological changes and inflammatory cytokine expression were significantly reduced in RAW264.7 cells subjected to OLED treatment compared to the LPS-induced controls. This work provides evidence for the anti-inflammatory effects of OLEDs, demonstrating their potential to be incorporated into medical devices in the future.